Changes in plasma angiotensin-converting enzyme activity and noradrenaline responses to long-term nitric oxide inhibition vary depending on their basal values in chickens - Aksulu, HE; Bingöl, I; Karatas, F; Sagmanligil, H; Üstündag, B (Acad Sciences Czech Republic, Inst Physiology, 2000)
In this study, we investigated the effects of N omega-nitro-L-arginine (L-NNA) on arterial blood pressure (BP), plasma noradrenaline (NA) and adrenaline (A) levels and angiotensin-converting enzyme (ACE) activity. L-NNA was applied with tap water (1 mg/ml) from the 3rd to the 8th week of age (group L-NNA(1)). In Experiment I, long-term L-NNA application increased BP compared to the control group (group CI) (L-NNA(1) = 131.4 +/- 6.3, n=6; C-1= 82.7 +/- 4.7 mm Hg, n=7) but decreased plasma noradrenaline and adrenaline levels and ACE activity (NA levels: C-1 = 15.5 +/- 0.8, n=7; L-NNA(1)= 8.6 +/- 0.5 ng/ml, n=7; A levels: C-1 = 15.5 +/- 0.8, n=7; L-NNA(1) = 6.0 +/- 0.5 ng/ml, n=7; ACE activities: C-1= 87.3 +/- 3.1, n=6; L-NNA(1) = 46.2 +/- 1.9 U/l, n=5). On the other hand, in Experiment 2 (carried out under the same conditions and in age-matched chickens), blood pressure, plasma noradrenaline levels and ACE activity were found to differ in the control group (C-2) (BP=141.4 +/- 15.5 mm Hg, n=7; NA =1.1 +/- 0.4 ng/ml, n=7; ACE = 57.2 +/- 5.3 U/l, n=7) as compared to CI, while plasma adrenaline levels were similar. In this series, long-term L-NNA application (group L-NNA(2)) did not change the BP, but surprisingly increased noradrenaline and ACE values (values of L-NNA(2): BP = 165.7 +/- 15.6 mm Hg, n=7; NA = 9.3 +/- 1.3 ng/ml, n=8; ACE = 149.3 +/- 16 U/l, n=8) while decreasing plasma adrenaline levels. L-arginine addition to L-NNA treatment completely reversed plasma noradrenaline and ACE activity values. These results indicate the modulatory activity of an L-arginine-NO pathway on adrenaline release as well as on the renin-angiotensin system in chickens.
Keywords: blood pressure; N-omega-nitro-L-arginine; adrenaline; noradrenaline; angiotensin-converting enzyme; chicken